A rare intronic c.2654+1G>A mutation in CSF1R-microglial encephalopathy: a case report - Wu, HongYan; Shi, JingYu; Wang, XiaoShan; Yang, Mei; Cai, Jing (Frontiers in Genetics, 2025)
ObjectiveWe report a case of CSF1R-microglial encephalopathy associated with a rare intronic c.2654 + 1G>A mutation, featuring negative diffusion-weighted imaging (DWI) findings and a cerebrospinal fluid (CSF) biomarker profile indicative of Alzheimer’s disease-related changes, and we explore the associations between genetic mutations, CSF biomarker alterations, and neuroimaging manifestations.MethodsThis study documents the demographic data, detailed medical history, and clinical manifestations of a patient with CSF1R-microglial encephalopathy. The medical histories of some family members were collected, and the proband underwent whole-exome sequencing (WES) for diagnostic confirmation.ResultsThe patient, a 53-year-old woman, presented with early-onset cognitive decline, personality changes, and behavioral abnormalities. Neuropsychological testing revealed severe cognitive impairment, and the CSF biomarker profile suggested Alzheimer’s disease-related changes. Cranial MRI showed bilateral, symmetric deep white matter changes, brain atrophy (including corpus callosum thinning), and low signal intensity on DWI. Family history revealed that 3 out of 19 individuals across four generations, including the proband, her aunt, and her sister, developed dementia and progressed to severe cognitive impairment rapidly. WES analysis revealed a heterozygous c.2654 + 1G>A variant in the CSF1R gene (NM_005211.3), confirming a diagnosis of CSF1R-microglial encephalopathy caused by a dominant autosomal mutation in exon 20 of the CSF1R gene.ConclusionCSF1R-microglial encephalopathy is a progressive disorder with diverse early clinical presentations, making it prone to misdiagnosis and delayed treatment. This case suggests that, contrary to previous findings, negative DWI results should not exclude CSF1R-microglial encephalopathy. In addition, CSF biomarker profiles in patients with CSF1R-microglial encephalopathy may exhibit Alzheimer’s disease-related changes. Early genetic testing is critical, and for genetically linked diseases, testing other family members can help ensure early diagnosis and intervention.